Distribution of D543N NRAMP1 polymorphism in tuberculosis patients from Kupang, east region of Indonesia (Medical Journal of Indonesia, 2012)
Background: Natural resistance associated macrophage protein (NRAMP) is a proton/ divalent cation transporter which play a role in iron trafficking in the phagosomes. Variations in NRAMP1 gene have been reported to be associated with susceptibility to tuberculosis (TB) because Mycobacterium tuberculosis (MTb), the causative agent of TB, compete with its host to uptake iron for its metabolism. The study aimed to describe the polymorphism of NRAMP among TB patients in Kupang, East Nusa Tenggara. Methods: This is a case-control study, cases were pulmonary TB, new patients, aged 15-55 years with sputum smear positive for acid fast bacili. Control were surrounding neighbours without symptoms and history of TB. All demographic information and blood sample were taken for polymorphism. PCR/RFLP method was performed to explore whether single nucleotide polymorphism D543N of NRAMP1 gene is associated with susceptibility to TB. Results: The study involved 64 pulmonary TB patients and 51 healthy controls. We observed a significant different in the distribution of NRAMP1 genotypes frequencies between TB patients and healthy controls (p = 0.014). Moreover, D543N polymorphism gave significant association only in male subjects. Though the numbers of the subjects are limited, D543N NRAMP1 polymorphism in endemic region in Kupang, the eastern part of Indonesia, seems to be associated with the susceptibility to TB. This is in contrary to studies reported in other part of Indonesia: i.e from west part (Jakarta, Bandung) and central part (Makassar). The population from Kupang may similar genetic background as African population, as Mycobacterium infected in population from Kupang is mostly Mycobacterium africanum. Increasing the number of subjects may enhance the power of the study and possibility to meet Hardy-Weinberg Equilibrium to detect the true associations of this polymorphism in susceptibility to TB. Conclusion: There was a significant difference of polymorphism NRAMP1 which more pronounced among male subjects, however this has not yet fulfilled the Hardy-Weinberg equilibrium. (Med J Indones. 2012;21:160-5)